Psycho-Emotional Violence, Its Association, Co-Occurrence, and Bidirectionality with Cyber, Physical and Sexual Violence - Paat, Yok-Fong (J Child Adolesc Trauma, 2019)
Using data from a cross-sectional sample of seventh to twelfth graders who attended northeastern schools between 2011 and 2012, we examined the associations between psycho-emotional dating violence and cyber, physical, and sexual violence Overall, we found that respondents experienced more than one type of dating violence simultaneously, indicating the prevalence of co-occurrence in dating violence. Further, being a victim of psycho-emotional violence was associated with perpetrating similar types of violence, suggesting the bidirectional nature of this type of aggression. Among the covariates, we found that peer bullying, cyber bullying, cell phone usage, the respondents’ age, gender, and grades were risk factors for psycho-emotional violence. The findings may be used to guide dating violence intervention efforts and the development of school based and family-oriented treatment plans.